2015
DOI: 10.2174/1874325001509010283
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of Polytrauma Patients: The Management of Massive Skeletal Bleeding

Abstract: The term ‘severely injured patient’ is often synonymous of polytrauma patient, multiply-injured patient or, in some settings, polyfractured patient. Together with brain trauma, copious bleeding is the most severe complication of polytrauma. Consequently hypotension develop. Then, the perfusion of organs may be compromised, with the risk of organ failure. Treatment of chest bleeding after trauma is essential and is mainly addressed via surgical manoeuvres. As in the case of lesions to the pelvis, abdomen or ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…ExFix provides more stability than binders, avoiding anterior abdominal cavity compression and also the risk of skin necrosis[45]. When properly applied, ExFix facilitates laparotomy, stabilising the pelvic bones[6,7]. However, the ExFix technique is much more time-consuming and aggressive.…”
Section: Resuscitationmentioning
confidence: 99%
See 3 more Smart Citations
“…ExFix provides more stability than binders, avoiding anterior abdominal cavity compression and also the risk of skin necrosis[45]. When properly applied, ExFix facilitates laparotomy, stabilising the pelvic bones[6,7]. However, the ExFix technique is much more time-consuming and aggressive.…”
Section: Resuscitationmentioning
confidence: 99%
“…When there is major retroperitoneal bleeding that remains uncontained after pelvic ring closure, the indicated approach could be packing or embolisation[6,7]. However, since pelvic ring closure produces a tamponade effect, stabilises the pelvis and occludes fractures, thus enhancing cessation of the haemorrhage, pelvic stabilisation is advised before any attempts are made at packing or embolisation[6,7,37], although if necessary the latter could be performed even in the case of an unfixed, unstable pelvic fracture[61].…”
Section: Resuscitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies suggested that angiography with subsequent embolization and immediate external fixation should be performed to control the bleeding of pelvic fracture. 2 , 7 , 8 But the incidence of pelvic fracture patients who need the embolization treatment is estimated to be less than 10%, 2 , 9 and the application of embolization under the guidance of angiography is only efficacious in addressing arterial haemorrhage which only presents in 15% of lethal pelvic fractures. 10 Moreover, the procedures of embolization under the guidance of angiography can be time-consuming and the treatment for other associated injuries would be delayed.…”
Section: Introductionmentioning
confidence: 99%